Strengthening the Performance of Micro, Small, and Medium Enterprises (MSMEs) Through Social Media Adoption with Human Resource Competency as Moderation and Implementation of The Penta Helix Model in Facing New Normal Challenges in Jember Regency: (Model Penguatan Kinerja UMKM Melalui Adopsi Media Sosial dengan Kompetensi SDM sebagai Moderasi serta Implementasi Penta Helix dalam Menghadapi Tantang New Normal di Kabupaten Jember) - Mawardi, Ahmad Ahsin Kusuma; Farida, Lilik; Nusbantoro, Ariwan Joko; Utami, Elok Sri; Endhiarto, Tatok; Apriliana, Tria (e-Journal Ekonomi Bisnis dan Akuntansi, 2024)
The Covid-19 pandemic has had a negative impact on MSMEs, and has encouraged MSMEs to be more creative in trying to maintain and develop their business during the pandemic, especially through the adoption of social media for marketing activities. However, the competence of HR in MSMEs is still an obstacle to the process of adopting social media. The aims of this study were (1) to analyze the role of HR competence in moderating social media adoption on MSME performance, and (2) to analyze the implementation of the pentahelix model in strengthening MSME performance through the role of social media adoption and HR competence in facing the new normal challenges in Jember Regency. The research method used is mixed method research, which combines both quantitative and qualitative research approaches. The sample of this research is 100 SMEs. Quantitative data analysis was carried out using the PLS SEM technique. Qualitative data analysis was carried out with FGDs with stakeholders such as the government represented by the Jember District Office of Cooperatives and MSMEs, the media, the MSME community, academics, and business people. The results of the verification analysis using the SEM analysis technique show that technology has a significant effect on the performance of MSMEs in Jember Regency. Meanwhile, organizational, and environmental variables did not have a significant effect on the performance of MSMEs in Jember Regency. HR competence has a significant effect on the performance of MSMEs in Jember Regency. HR competence does not moderate the effect of technology on the performance of MSMEs in Jember Regency. HR competence does not moderate organizational influence on MSME performance in Jember Regency. HR competence does not moderate the influence of the environment on the performance of MSMEs in Jember Regency. To strengthen the performance of MSMEs through the adoption of social media, all stakeholders have an important role, where the government becomes a facilitator in conducting training and mentoring. With the involvement of academics to conduct research so that market segmentation is more appropriate for marketing through social media. Then businesspeople who have been involved in digital marketing play a role in transferring knowledge, and the role of the media is to strengthen marketing carried out by MSMEs through social media.